Estudio del comportamiento de consumo horario residencial de agua potable de la ciudad de Machachi. - Guanolema Maroto, Henrry Geovanny (2026)
Having clean, safe drinking water is of utmost importance for the quality of life and the growth of cities. Specifically in Machachi, population growth and the water supply system are affecting hourly per capita water consumption, so it is important to understand this pattern to improve resource management and distribution. The main purpose of this research is to assess hourly water consumption patterns in the residential sector of Machachi, thereby identifying water use patterns and improving supply planning. To achieve this, a socioeconomic stratification of the population was carried out to classify residential areas and the level of concentration of distribution networks. In addition, field measurements were conducted using residential wáter meters, with consumption data collected over 7 days, 24 hours a day, to construct a representative profile of use. The approach is considered a case study, as it was implemented in a specific social context and integrated quantitative and qualitative analyses of meters installed across three distribution sectors: Machachi, Aloasí, and Tucuso. According to the study, users use water resources more between 6:00 a.m. and 9:00 a.m. and 6:00 p.m. and 9:00 p.m., which coincide with the execution of both domestic and commercial activities. The Machachi network has the highest average consumption, followed by Aloasí and Tucuso, the latter with lower consumption due to urbanization. Therefore, it is essential to implement an optimization plan for the distribution of drinking water in Machachi to reduce waste and ensure an effective supply in all areas.